Integrating Digital Forensics Techniques into Curatorial Tasks: A Case Study - Sam Meister; Alexandra Chassanoff (International Journal of Digital Curation, 2014)
In this paper, we investigate how digital forensics tools can support digital curation tasks around the acquisition, processing, management and analysis of born-digital materials. Using a real world born-digital collection as our use case, we describe how BitCurator, a digital forensics open source software environment, supports fundamental curatorial activities such as secure data transfer, assurance of authenticity and integrity, and the identification and elimination of private and/or sensitive information. We also introduce a workflow diagram that articulates the processing steps for institutions processing born-digital materials. Finally, we review possibilities for further integration, development and use of digital forensic tools.